Development of Heart Rate Variability Analysis Device for Human Body Stress Level Indication - Hishamuddin, Nurin Asyiqin; Mokhtar, Mohd Hezri (Progress in Engineering Application and Technology, 2024)
The COVID-19 pandemic has affected people’s lives worldwide, and Malaysia also has a hard time facing the pandemic. The pandemic has caused many businesses such as hotel and tourism industries to shut down their operation and reduce costs by dismissing their workers. Losing a job can cause a feeling stress issue. Heart Rate is one of the famous investigative tools to identify stress levels for the past decades with various measuring methods. Therefore, these projects present a suitable method of measuring the Heart Rate using heart rate sensors. An AD8232 ECG sensor was used as a heart rate sensor which connected to Arduino MEGA to send the data for further analysis in a computer. In the computer, PyCharm software has been used to analyze the data using a Heart Rate measurement method to determine the Heart Rate. Then, the Heart Rate was chosen to determine the user stress level based on the Firstbeat baseline. A test consisting of six test subjects consisting of males and females. As a result, all of the test subject result indicates a normal stress level under resting conditions. The result was displayed in the designed PyCharm with some additional features such as ECG recording and save data function, which stores all the users’ results in Microsoft Excel format.